The effect of bleaching agents on the microhardness of dental aesthetic restorative materials - (:unkn) unknown (BLACKWELL PUBLISHING LTD, 2002)
This study investigated the effects of three home bleaching agents on the microhardness of various dental aesthetic restorative materials. The restorative materials were: feldspatic porcelain, microfilled composite resin and light-cured modified glass-ionomer cement and the bleaching agents Nite-White (16% carbamide peroxide), Opalescence (10% carbamide peroxide and carbapol jel) and Rembrandt (10% carbamide peroxide jel). A total of 90 restorative material samples were prepared 1 cm diameter and 6 mm thick and kept in distilled water for 24 h before commencing bleaching which was carried out for 8 h day(-1) for 4 weeks. Microhardness measurements were then made using a Tukon tester. Statistically significant differences with respect to unbleached controls were found only for the feldspatic porcelain and microfilled composite resins (P<0.05) for Nite-White and Opalescence. All the bleaching agents decreased the microhardness of the porcelain and increased that of the light cured modified glass-ionomer cement. For the composite resin, whereas Nite-White increased its microhardness, the other bleaching agents decreased it. There were no significant differences between the bleaching agents for any of the restorative materials.
Keywords: bleaching agents; microhardness; aesthetics restorative materials